“My Neighborhood Is Watching Me”: The Role of Neighborhood Processes in the Offending and Self-Control–Crime Nexus - Kafafian, Matthew (Criminal justice and behavior, 2023)
Using survey data from a sample of 1,435 Ukrainian and Russian adults, this study examines the interplay between collective processes, individual-level self-control, and offending. Multilevel regression models estimate the direct effects of neighborhood-level self-control, perceptions of sanction risks, and strain on criminal behavior, showing how these contextual factors condition the association between individual-level self-control and offending. Findings suggest that collective self-control and perceived sanction risks are important moderators of the self-control–crime relationship at the individual level, highlighting the protective effect of high self-control on offending in neighborhoods with strong collective self-control and sanctioning climates. Overall, the study stresses the importance of exploring the role of neighborhood processes beyond social disorganization in the self-control–crime nexus.